SOME MEGASPORES FROM SOUTH AFRICA AND AUSTRALIA - Dijkstra, S. J. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1972)
Dr. Plumstead has sent a number of samples from South Africa to us for maceration of the spores from them and for an attempt to determine the horizons from the megaspores only. Other details were not given. In addition to these samples we had some from Australia, and it became very interesting to compare the spores from S. Africa with those from Australia or other Gondwana deposits in India or Brasil.